1991
DOI: 10.1016/0014-5793(91)80135-p
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of cytochrome P‐450scc with cytochrome bs

Abstract: Received 26 No~rnb~r I~)0 ,~r.~trophcstometrl¢, ~lttntt)r ~,hromalOllr~phy and eros~,hnklnil exl~rm~nls provided e~M,~nu Ih~t cyh~hton~ P,4~0w¢ fron'~ b~ln¢ ~dren~ort). ¢al mtt~htmdrta farms a Iqlhl eumple~c with =yt~hrame ~ from r~bblt h~er rnlcrmomes l)~ the r~or, s0tuled system fholest=r¢~l aside chain acthrlly ol'c)'tuchrome P-4SOscc was ~nhanc~l b~' the atldlllOn of~yt~hrorne b, Cyt~hrome P.4~IO,~, Cytoehf~me b,, t.:~mplex formation, Arltnhy ~hromatollraph),, Chemical woss.hnklnll I, INTRODUCTIONCytochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…3B. In agreement with earlier reports (27), the presence of b5 results in an Ϸ2-fold stimulation of CYP11A1. (25,26,28) with the 1D 1 H NMR spectra of D3 (Fig.…”
Section: The Conversion Of Large Amounts Of D3 To Hydroxylated Productssupporting
confidence: 92%
See 1 more Smart Citation
“…3B. In agreement with earlier reports (27), the presence of b5 results in an Ϸ2-fold stimulation of CYP11A1. (25,26,28) with the 1D 1 H NMR spectra of D3 (Fig.…”
Section: The Conversion Of Large Amounts Of D3 To Hydroxylated Productssupporting
confidence: 92%
“…This problem prompted us to test ways of increasing the yield of D3 products. It has been reported that the addition of purified rat liver microsomal b5 to a reaction mixture containing the reconstituted CYP11A1 system increases the rate of cholesterol metabolism (27). Fig.…”
Section: Identification Of the Product Formed During The Metabolism Omentioning
confidence: 96%
“…Most controversial and least understood is the mechanism by which b 5 stimulates some P450-catalyzed reactions but not others (5). The direct interaction of b 5 with CPR (54-57) and different forms of microsomal P450s (58-65), as well as with mitochondrial and bacterial types of P450, such as P450cam (66, 67) and P450scc (68), has been shown. The primary structure of b 5 has been determined by direct protein sequencing (69)(70)(71) and confirmed by the deduced amino acid sequence determined from the nucleotide sequence of cDNA (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…Tescil davasında, zilyet, olağanüstü zamanaşımıyla kazanım şartlarını sağladığına ilişkin ispat yükü altındadır 79 . Zilyetliğin ispatı konusunda, tapulu taşınmazlar bakımından herhangi bir kısıtlama mevcut olmayıp, her türlü delille ispat söz konusu olabilmektedir 80 . Ancak, tapusuz taşınmazların ispatı, taşınmazın sulu toprak veya kuru toprak olmasına göre farklılık göstermektedir 81 .…”
Section: Introductionunclassified